Large-scale ultrafast synthesis of nickel-iron oxide catalyst and application of nickel-iron oxide catalyst in upgrading and recycling of PET (Polyethylene Terephthalate) plastics

Through the large-scale ultra-fast synthesis method of nickel-iron oxide catalyst, the problems of low recovery rate and high catalyst cost are solved, and the high efficiency electrocatalytic oxidation of PET plastics is achieved, with high product selectivity, suitable for industrial production, and high value chemical products.

CN120330766APending Publication Date: 2025-07-18OCEAN UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510626156.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

In the prior art, PET plastics have low recovery rate, poor selectivity, high catalyst cost and cannot be produced on a large scale, resulting in low degradation efficiency of PET plastics and difficult to achieve the production of high value-added products.

Method used

A large-scale ultrafast synthesis method of nickel-iron oxide catalyst was adopted to form NiFeOx/NF-3 catalyst by pretreatment of foam nickel substrate, loading NiFe-LDH and annealing, and electrolyzing the PET hydrolysis solution in an alkaline environment, and collecting formate and potassium terephthalate from the anode to achieve efficient electrocatalytic ethylene glycol oxidation.

Benefits of technology

It realizes high-efficiency electrocatalytic oxidation of PET plastics, has high product selectivity, reduces potential demand, is suitable for industrial production, produces high-value chemical products, and has wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120330766A_ABST
    Figure CN120330766A_ABST
Patent Text Reader

Abstract

The invention discloses large-scale ultrafast synthesis of a nickel-iron oxide catalyst and application of the nickel-iron oxide catalyst in upgrading and recycling of PET (polyethylene terephthalate) plastics, the catalyst takes foamed nickel as a carrier, NiFe-LDH is loaded on the carrier, then annealing is performed to form a metal oxide recorded as NiFeOx / NF-3, and the catalyst can oxidize ethylene glycol into formate with high yield and high Faraday efficiency in an alkaline environment. In a flowing electrolytic cell, plastic degradation is carried out by taking a waste plastic hydrolysis solution as an electrolyte, the catalyst as an anode catalyst and platinum-carbon-loaded foamed nickel as a cathode catalyst. In the constant-voltage reaction process, hydrogen can be collected at the cathode, formate and potassium terephthalate are obtained at the anode, and potassium diformate and terephthalic acid are obtained after acidification treatment. The catalyst is simple to synthesize, can be produced on a large scale, not only reduces the potential of the anodic reaction, but also can convert the waste plastics into high value-added chemicals as industrial raw materials, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of electrolytic water hydrogen production technology and electrochemical catalytic oxidation of PET plastics, and particularly relates to a large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst and its application in the upgrading and recycling of PET plastics. Background Art

[0002] The good performance characteristics of PET facilitate people's daily lives, but its durability has also become the main source of white pollution. The natural degradation life of PET can reach hundreds of years, seriously threatening the safety of water and soil and the physical and mental health of humans. At present, the recovery rate of PET mainly relies on mechanical methods, and the recycled PET materials are downgraded as low-usage materials, resulting in a huge waste of materials.

[0003] Using electrochemical methods to recycle and upgrade PET is a mild and efficient method that can produce high-purity and economically viable high-value-added products, having a positive impact on the environment. PET can be effectively decomposed into monomer components by alkali or hydrolase, and its long molecular chains can be cleaved into small organic molecules. These monomers, such as ethylene glycol (EG), can be converted into formate (FA) or glycolic acid (GA) by electrochemical methods, and hydrogen fuel can be obtained simultaneously. This chemical cycle is theoretically expected to achieve the recycling of waste plastics and has received extensive attention from the scientific and industrial communities in recent years.

[0004] The efficiency of this electrochemical method depends on the selectivity of the catalyst for the oxidation reaction of PET hydrolysis monomers (EG) and the production cost of the catalyst. In addition, whether the catalyst can be produced on a large scale is also crucial. At present, for the degradation research of PET plastics, although the methods are perfect, there are still problems such as low space survival rate, poor product selectivity, and inability to be produced on a large scale. Developing low-cost and highly efficient catalytic materials for ethylene glycol oxidation reaction is crucial for the upgrading and recycling application of PET plastic degradation.

[0005] The present invention designs a large-scale and ultrafast synthesis of a nickel-iron oxide catalyst and its application in the upgrading and recycling of PET plastics to solve the above technical problems. Summary of the Invention

[0006] Aiming at the shortcomings and deficiencies of the above-mentioned existing technologies, the present invention provides a large-scale and ultrafast synthesis of nickel-iron oxide catalysts and their application in the upgrading and recycling of PET plastics. The present invention aims to solve the problems of low recovery rate, poor selectivity, high catalyst cost, and downgraded use of products in current waste plastics recycling. The preparation method provided by the present invention is simple and has low preparation cost, and is suitable for industrial batch production. After the waste plastics are hydrolyzed by an alkaline solution, potassium terephthalate and ethylene glycol are generated, and ethylene glycol is further catalytically oxidized to formate during the electrolysis process. The present invention provides a method that can efficiently electrocatalyze the oxidation of ethylene glycol to improve the efficiency of plastic upgrading and recycling.

[0007] To achieve the above object, the present invention provides the following technical solutions: A large-scale and ultrafast synthesis of nickel-iron oxide catalysts and their application in the upgrading and recycling of PET plastics, including the following steps:

[0008] S1. Pretreat the nickel foam substrate;

[0009] S2. Immerse the dried nickel foam into a 30 ml mixed solution of ferric chloride hexahydrate and nickel chloride hexahydrate, take it out after a short time, use filter paper to absorb the excess solution on the surface, and air-dry it naturally at room temperature to obtain NiFe-LDH grown on the nickel foam;

[0010] S3. Put the NiFe-LDH grown on the nickel foam obtained in step S2 into a tubular furnace, anneal it in a protective atmosphere, keep it warm for a period of time and then naturally cool to room temperature to obtain the NiFeOx / NF-3 catalyst for PET plastic upgrading and recycling;

[0011] S4. Apply the NiFeOx / NF-3 catalyst obtained in step S3 in a flow cell for the upgrading and recycling of PET plastics. First, add PET plastics to a potassium hydroxide solution for hydrolysis, use the hydrolysis product as the electrolyte for constant voltage electrolysis, collect the electrolysis product at the anode, and obtain high-value-added industrial chemicals after treatment.

[0012] Based on the above technical solutions, in step S1, the pretreatment of the nickel foam substrate is specifically operated as follows: First, immerse the nickel foam substrate in hydrochloric acid and perform ultrasonic treatment to remove the oxide film on its surface; then ultrasonically treat the nickel foam substrate in deionized water to remove the residual hydrochloric acid, then ultrasonically treat it with ethanol, and then vacuum dry it to complete the pretreatment of the nickel foam substrate.

[0013] Based on the above technical solutions, in step S1, the nickel foam has a thickness of 1.6 mm and an area of 2 * 3 cm 2 。

[0014] Based on the above technical solutions, in step S1, the concentration of hydrochloric acid is 3 mol·L -1 。

[0015] On the basis of the above technical solution, in step S1, the ultrasonic treatment time with hydrochloric acid is 15 - 20 min, the ultrasonic treatment time with deionized water is 10 - 15 min, and the ultrasonic treatment time with ethanol is 5 - 10 min.

[0016] On the basis of the above technical solution, in step S2, the concentration of ferric chloride hexahydrate in the mixed solution is 0.5 mol·L -1 , and the concentration of nickel chloride hexahydrate is 0.5 mol·L -1 .

[0017] On the basis of the above technical solution, in step S2, the immersion time of nickel foam in the solution is 90 seconds.

[0018] On the basis of the above technical solution, in step S3, the protective atmosphere is nitrogen or argon, the annealing temperature is 300 °C, and the heating rate is 5 °C·min -1 , and the holding time is 2 hours.

[0019] On the basis of the above technical solution, in step S4, the concentration of potassium hydroxide for hydrolyzing PET waste plastics is 3 mol·L -1 .

[0020] On the basis of the above technical solution, in step S4, the product after PET hydrolysis is a mixed solution of potassium terephthalate and ethylene glycol.

[0021] On the basis of the above technical solution, in step S4, the treatment of the anodic electrolysis product is acidification, filtration, and rotary evaporation.

[0022] In a second aspect, the present invention provides a nickel-iron oxide catalyst, which is prepared by the large-scale ultrafast synthesis method of a nickel-iron oxide catalyst according to any one of the above embodiments.

[0023] In a third aspect, the present invention provides an application of the large-scale ultrafast synthesis method of a nickel-iron oxide catalyst according to any one of the above embodiments in the upgrading and recycling of PET plastics.

[0024] Compared with the related technology, the beneficial effects of the present invention are as follows:

[0025] (1) The preparation method of the catalyst provided by the present invention is simple and efficient, with a short time period, can be produced on a large scale, and can better meet the requirements of industrial large-scale production.

[0026] (2) In the present invention, waste plastics are catalytically oxidized into potassium formate and potassium terephthalate by an electrocatalytic method and hydrogen production is coupled. While producing high-value chemical products, the voltage for hydrogen production is reduced, which has greater economic benefits than other methods and is more suitable for industrialization and large-scale promotion. The present invention can be carried out at normal temperature and pressure, with high product selectivity and conversion rate, suitable for industrial implementation, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the accompanying drawings required for the description of the embodiments or the prior art. Obviously, the accompanying drawings in the following description are only one embodiment of the present invention. For those of ordinary skill in the art, without creative efforts, other implementation drawings can be obtained according to the provided drawings.

[0028] Figure 1 It is the flow chart of PET degradation of the present invention and the application of NiFeOx / NF-3 prepared in Example 1 as an electrolytic catalyst in the upgrading and recycling of PET plastics;

[0029] Figure 2 It is the preparation flow chart of NiFeOx / NF-3 prepared in Example 1 of the present invention and NiFeOx / NF-1, NiFeOx / NF-2, NiFeOx / NF-4, NiFeOx / NF-5 obtained in Comparative Example 1-4;

[0030] Figure 3 It is the scanning electron microscope photo of NiFeOx / NF-3 prepared in Example 1 of the present invention;

[0031] Figure 4 It is the XRD spectrum of NiFeOx / NF-3 prepared in Example 1 of the present invention and NiFeOx / NF-5 obtained in Comparative Example 4;

[0032] Figure 5 It is the LSV test chart of EGOR of Example 1 of the present invention and Comparative Example 1-4 under three electrodes;

[0033] Figure 6 It is the Tafel performance chart of EGOR of Example 1 of the present invention and Comparative Example 1-4 under three electrodes;

[0034] Figure 7 It is the impedance performance chart of EGOR of Example 1 of the present invention and Comparative Example 1-4 under three electrodes;

[0035] Figure 8 It is the I-T curve test chart of NiFeOx / NF-3 prepared in Example 1 of the present invention at different potentials;

[0036] Figure 9 It is the Faraday efficiency and formic acid production graph after I-T test of NiFeOx / NF-3 prepared in Example 1 of the present invention at different potentials;

[0037] Figure 10 It is the continuous electrolysis graph of NiFeOx / NF-3 prepared in Example 1 of the present invention at a potential of 1.6V;

[0038] Figure 11 It is the Faraday efficiency graph of each cycle during the continuous electrolysis of NiFeOx / NF-3 prepared in Example 1 of the present invention at a potential of 1.6V;

[0039] Figure 12 It is the LSV performance graph of EGOR and OER measured for NiFeOx / NF-3 prepared in Example 1 of the present invention in a flow cell;

[0040] Figure 13 It is the XRD spectrum of the product KDF obtained after electrolysis and treatment using the PET hydrolysis product as the electrolyte for NiFeOx / NF-3 prepared in Example 1 of the present invention in a flow cell. Detailed implementation manners

[0041] The present invention will be further described below in conjunction with the drawings and examples:

[0042] The embodiments of the present invention will be described in detail below. Examples of the embodiments are shown in the drawings, where the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below by referring to the drawings are exemplary and are only used to explain the present invention and should not be construed as limiting the present invention.

[0043] In the description of the present invention, it should be noted that unless otherwise clearly specified and defined, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected, or indirectly connected through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific situations.

[0044] In the description of the present invention, it should be understood that the orientation or positional relationship indicated by the terms "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as limiting the present invention.

[0045] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.

[0046] Unless otherwise specified, the materials, reagents, etc. used in the following examples can all be obtained from commercial sources.

[0047] The large-scale and ultrafast synthesis of a nickel-iron oxide catalyst and its application in the upgrading and recycling of PET plastics, characterized in that the preparation method comprises the following steps:

[0048] S1. Pretreat the nickel foam substrate;

[0049] S2. Immerse the dried nickel foam into a mixed solution of 30 ml of ferric chloride hexahydrate and nickel chloride hexahydrate, take it out after a short time, use filter paper to absorb the excess solution on the surface, and air-dry it naturally at room temperature to obtain NiFe-LDH grown on the nickel foam;

[0050] S3. Put the NiFe-LDH grown on the nickel foam obtained in step S2 into a tubular furnace, anneal it in a protective atmosphere, keep it warm for a period of time and then cool it naturally to room temperature to obtain the NiFeOx / NF-3 catalyst for the upgrading and recycling of PET plastics;

[0051] S4. Apply the NiFeOx / NF-3 catalyst obtained in step S3 to the upgrading and recycling of PET plastics in a flow cell. First, add PET plastics to a potassium hydroxide solution for hydrolysis, use the hydrolysis product as an electrolyte for constant voltage electrolysis, collect the electrolysis product at the anode, and obtain high-value-added industrial chemicals after treatment.

[0052] Based on the above technical solution, in step S1, the specific operation of the pretreatment of the nickel foam substrate is as follows: First, soak the nickel foam substrate in hydrochloric acid and perform ultrasonic treatment to remove the oxide film on its surface; then ultrasonically treat the nickel foam substrate in deionized water to remove the residual hydrochloric acid, then ultrasonically treat it with ethanol, and then vacuum dry it to complete the pretreatment of the nickel foam substrate.

[0053] Based on the above technical solution, in step S1, the thickness of the nickel foam is 1.6 mm and the area is 2 * 3 cm 2 。

[0054] Based on the above technical solution, in step S1, the concentration of hydrochloric acid is 3 mol·L -1 。

[0055] Based on the above technical solution, in step S1, the ultrasonic treatment time of hydrochloric acid is 15 - 20 min, the ultrasonic treatment time of deionized water is 10 - 15 min, and the ultrasonic treatment time of ethanol is 5 - 10 min.

[0056] Based on the above technical solution, in step S2, the concentration of ferric chloride hexahydrate in the mixed solution is 0.5 mol·L -1 , and the concentration of nickel chloride hexahydrate is 0.5 mol·L -1 .

[0057] Based on the above technical solution, in step S2, the immersion time of nickel foam in the solution is 90 seconds.

[0058] Based on the above technical solution, in step S3, the protective atmosphere is nitrogen or argon, the annealing temperature is 300 °C, and the heating rate is 5 °C·min -1 , and the holding time is 2 hours.

[0059] Based on the above technical solution, in step S4, the concentration of potassium hydroxide used for hydrolyzing PET waste plastics is 3 mol·L -1 .

[0060] Based on the above technical solution, in step S4, the product after PET hydrolysis is a mixed solution of potassium terephthalate and ethylene glycol.

[0061] Based on the above technical solution, in step S4, the treatment of the anodic electrolysis product is acidification, filtration, and rotary evaporation.

[0062] Second, the present invention provides a nickel-iron oxide catalyst, which is prepared by the large-scale ultrafast synthesis method of a nickel-iron oxide catalyst according to any one of the above embodiments.

[0063] Third, the present invention provides an application of the large-scale ultrafast synthesis method of a nickel-iron oxide catalyst according to any one of the above embodiments in the upgrading and recycling of PET plastics.

[0064] Example 1

[0065] S1. Pretreatment of nickel foam substrate: Take nickel foam (NF) with a thickness of 1.6 mm and an area of 2*3 cm2. First, soak the nickel foam in 3M hydrochloric acid and ultrasonically treat it for 15 min to remove the oxide film on its surface; then place the nickel foam in ultrapure water and ultrasonically treat it for 10 min to remove the residual acid; then place the nickel foam in absolute ethanol and ultrasonically treat it for 5 min to remove organic substances. Finally, place the nickel foam in a vacuum drying oven at 60 °C and vacuum dry it for 6 h to obtain clean nickel foam;

[0066] S2. Immerse the dried nickel foam in 30 ml of 0.5 mol·L -1 ferric chloride hexahydrate and 0.5 mol·L -1In a mixed solution of nickel chloride hexahydrate, it was taken out after 90 seconds, and the excess solution on the surface was blotted with filter paper and air-dried naturally at room temperature to obtain NiFe-LDH grown on nickel foam;

[0067] S3. The NiFe-LDH grown on the nickel foam obtained in step S2 was placed in a tubular furnace and annealed in a protective atmosphere. The holding temperature was 300 °C and the heating rate was 5 °C·min -1 , and the holding time was 2 hours. Subsequently, it was naturally cooled to room temperature to obtain the NiFeOx / NF-3 catalyst for the upgrading and recycling of PET plastics.

[0068] Comparative Example 1

[0069] This example has the same method as Comparative Example 1, and the same parts are omitted. The difference from Comparative Example 1 is that in this example, the holding temperature in step S3 is 100 °C, and the catalyst is named NiFeOx / NF-1.

[0070] Comparative Example 2

[0071] This example has the same method as Comparative Example 1, and the same parts are omitted. The difference from Comparative Example 1 is that in this example, the holding temperature in step S3 is 200 °C, and the catalyst is named NiFeOx / NF-2.

[0072] Comparative Example 3

[0073] This example has the same method as Comparative Example 1, and the same parts are omitted. The difference from Comparative Example 1 is that in this example, the holding temperature in step S3 is 400 °C, and the catalyst is named NiFeOx / NF-4.

[0074] Comparative Example 4

[0075] This example has the same method as Comparative Example 1, and the same parts are omitted. The difference from Comparative Example 1 is that in this example, the holding temperature in step S3 is 500 °C, and the catalyst is named NiFeOx / NF-5.

[0076] Figure 1 is the flow chart of PET degradation of the present invention and the application of NiFeOx / NF-3 prepared in Example 1 as an electrolysis catalyst in the upgrading and recycling of PET plastics. The process is as follows: PET is first hydrolyzed in an alkaline environment, and the PET hydrolysis products (PTA, EG) are used as the electrolyte. In a flow cell, NiFeOx / NF-3 prepared in Example 1 is used as the working electrode, and commercial catalyst platinum-carbon is used as the counter electrode for the electrolysis of EG in the electrolyte. Subsequently, the electrolysis products are acidified and filtered, and the solid filtered out is terephthalic acid (TPA), and the remaining liquid is rotary evaporated, and the solid collected is potassium diformate (KDF).

[0077] Figure 2 It is the preparation flow chart of Example 1 and Comparative Examples 1-4 of the present invention.

[0078] Figure 3 It is the scanning electron microscope photograph of NiFeOx / NF-3 in Example 1 of the present invention. It can be seen from Figure 3 that it presents a uniform nanosheet morphology.

[0079] Figure 4 XRD spectra of Example 1 and Comparative Example 4 of the present invention. It can be seen from Figure 4 that the crystal form of the catalyst corresponds well to NiO and Fe2O3. The crystallinity of Example 1 is lower than that of the comparative example because low-temperature oxidation inhibits crystallization.

[0080] Figure 5 It is the LSV test chart of EGOR under three electrodes obtained from Example 1 and Comparative Examples 1-4 of the present invention. It can be seen from Figure 5 that the overpotential of NiFeOx / NF-3 in Example 1 is lower and the current density is higher.

[0081] Figure 6 It is the Tafel slope performance chart of the EGOR performance of Example 1 and Comparative Examples 1-4 of the present invention. It can be seen from Figure 6 that the Tafel slope of NiFeOx / NF-3 in Example 1 is lower, indicating its faster reaction kinetics.

[0082] Figure 7 It is the impedance performance chart of the EGOR performance of Example 1 and Comparative Examples 1-4 of the present invention. It can be seen from Figure 7 that the impedance of NiFeOx / NF-3 in Example 1 is smaller, indicating its faster interfacial electron transfer rate.

[0083] Figure 8 It is the I-T curve test chart of NiFeOx / NF-3 prepared in Example 1 of the present invention at different potentials. It can be seen from Figure 8 that as the potential increases, the current density also increases. However, due to the faster consumption of EG, the current density will also decrease faster.

[0084] Figure 9 It is the Faraday efficiency and formic acid production chart after I-T test of NiFeOx / NF-3 prepared in Example 1 of the present invention at different potentials. It can be seen from Figure 9 that the Faraday efficiency of Example 1 can be maintained above 90% at different potentials, and the formic acid production can reach 2.1 mmol·cm -2 ·h -1 .

[0085] Figure 10This is the continuous electrolysis diagram of NiFeOx / NF-3 prepared in Example 1 of the present invention at a potential of 1.6V. Taking 5 hours as a cycle, EG is added to the electrolyte after each cycle. From Figure 10 It can be seen that within one cycle, as EG is consumed, the current density gradually decreases. After replenishing EG, the current density returns to the initial level, indicating that NiFeOx / NF-3 in Example 1 has excellent stability and selectivity.

[0086] Figure 11 This is the Faraday efficiency diagram of each cycle during the continuous electrolysis of NiFeOx / NF-3 prepared in Example 1 of the present invention at a potential of 1.6V. From Figure 11 It can be seen that the Faraday efficiency of NiFeOx / NF-3 in Example 1 can be maintained above 90% for 10 cycles.

[0087] Figure 12 This is the LSV performance diagram of EGOR and OER measured for NiFeOx / NF-3 prepared in Example 1 of the present invention in a flow cell. From Figure 12 It can be seen that compared with the OER reaction without EG, the overpotential of EGOR is advanced by about 300 mV, reflecting lower energy consumption of EGOR.

[0088] Figure 13 This is the XRD spectrum of the product KDF obtained after electrolysis and treatment using the PET hydrolysis product as the electrolyte for NiFeOx / NF-3 prepared in Example 1 of the present invention in a flow cell. From Figure 13 It can be seen that the prepared KDF is consistent with the KDF standard card, indicating that high-purity industrial chemical KDF can be prepared by this method.

[0089] The present invention has been described by way of example above, but the present invention is not limited to the above specific embodiments. Any modification or variation based on the present invention falls within the scope of protection required by the present invention.

Claims

1. Large-scale and ultrafast synthesis of a nickel-iron oxide catalyst and its application in the upgraded recycling of PET plastics, characterized in that, The preparation method includes the following steps: S1. Pretreat the nickel foam substrate; S2. Immerse the dried nickel foam in a mixed solution of 30 ml of ferric chloride hexahydrate and nickel chloride hexahydrate, take it out after a short time, use filter paper to absorb the excess solution on the surface, and air-dry it naturally at room temperature to obtain NiFe-LDH grown on the nickel foam; S3. Put the NiFe-LDH grown on the nickel foam obtained in step S2 into a tubular furnace, anneal it in a protective atmosphere, cool it naturally to room temperature after holding for a period of time to obtain the NiFeOx / NF-3 catalyst for the upgrading and recycling of PET plastics; S4. Apply the NiFeOx / NF-3 catalyst obtained in step S3 to the upgrading and recycling of PET plastics in a flow cell. First, add PET plastics to a potassium hydroxide solution for hydrolysis, use the hydrolysis product as the electrolyte for constant voltage electrolysis, collect the electrolysis product at the anode, and obtain high-value-added industrial chemicals after treatment.

2. The large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 1, characterized in that, The specific operation of the pretreatment of the nickel foam substrate in step S1 is as follows: First, immerse the nickel foam substrate in hydrochloric acid and perform ultrasonic treatment to remove the oxide film on its surface; then ultrasonically treat the nickel foam substrate in deionized water to remove the residual hydrochloric acid, then ultrasonically treat it with ethanol, and then vacuum dry it to complete the pretreatment of the nickel foam substrate.

3. A method for large-scale ultrafast synthesis of a nickel-iron oxide catalyst according to claim 2, characterized in that, The nickel foam has a thickness of 1.6 mm and an area of 2 * 3 cm 2 .

4. A large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 2, characterized in that, The hydrochloric acid concentration described is 3 mol·L -1 .

5. A large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 2, characterized in that The ultrasonic treatment time with hydrochloric acid is 15 - 20 min, the ultrasonic treatment time with deionized water is 10 - 15 min, and the ultrasonic treatment time with ethanol is 5 - 10 min.

6. A method for large-scale and ultrafast synthesis of a nickel-iron oxide catalyst according to claim 1, characterized in that, In the mixed solution described in step S2, the concentration of ferric chloride hexahydrate is 0.5 mol·L -1 , and the concentration of nickel chloride hexahydrate is 0.5 mol·L -1 .

7. A large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 1, characterized in that, The immersion time of the nickel foam in the solution in step S2 is 90 seconds.

8. A method for large-scale and ultrafast synthesis of a nickel-iron oxide catalyst according to claim 1, characterized in that, The protective atmosphere described in step S3 is nitrogen or argon, the annealing temperature is 300 °C, and the heating rate is 5 °C·min -1 , and the holding time is 2 hours.

9. A large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 1, characterized in that, The concentration of potassium hydroxide for hydrolyzing PET waste plastics described in step S4 is 3 mol·L -1 .

10. A large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 1, characterized in that, The product after hydrolysis of PET in step S4 is a mixed solution of potassium terephthalate and ethylene glycol.

11. A large-scale and ultrafast synthesis method of a nickel-iron oxide catalyst according to claim 1, characterized in that, The treatment of the anode electrolysis product in step S4 is acidification, filtration, and rotary evaporation.

12. A nickel-iron oxide catalyst, characterized in that, Prepared by the large-scale ultrafast synthesis method of a nickel-iron oxide catalyst according to any one of claims 1 to 11.

13. The large-scale ultrafast synthesis of a nickel-iron oxide catalyst according to any one of claims 1 to 11 and its application in the upgrading and recycling of PET plastics.